Altered expression and activation of signal transducers and activators of transcription (STATs) in hepatitis C virus infection: in vivo and in vitro studies. Issue 8 (24th August 2005) - Larrea, E; Aldabe, R; Molano, E; Fernandez-Rodriguez, C M; Ametzazurra, A; Civeira, M P; Prieto, J
Abstract : Background: Signal transducers and activators of transcription (STATs) play a critical role in antiviral defence. STAT3 is also important in cell protection against inflammatory damage. STAT proteins are activated by interferons and by hepatoprotective cytokines of the interleukin 6 superfamily, including cardiotrophin 1. Methods: We analysed the status of STATs in hepatitis C virus (HCV) infected livers and the relationship between expression and activation of STATs and HCV replication in Huh7 cells transfected with HCV genomic replicon. Results: STAT3α expression was reduced in HCV infected livers showing an inverse correlation with serum alanine aminotransferase. In patients with HCV infection, nuclear staining for phosphorylated STAT3 was faint in parenchymal cells (although conspicuous in infiltrating leucocytes), in contrast with strong nuclear staining in hepatocytes from control livers. Expression and activation of STAT1 (a factor activated by both interferon (IFN)-α and IFN-γ) were increased in HCV infected livers, particularly in those with high inflammatory activity. Conversely, phosphorylated STAT2 (a factor selectively activated by IFN-α) was undetectable in livers with HCV infection, a finding that was associated with marked downregulation of the two functional subunits of the IFN-α receptor. HCV replication in Huh7 cells caused STAT3α downregulation and blocked STAT3 phosphorylation by either IFN-α or cardiotrophin 1. HCV replication in Huh7 cells also inhibited STAT1 and STAT2 activation by IFN-α while there was no impairment of STAT1 phosphorylation by the proinflammatory cytokine IFN-γ. Conclusions: STAT3 is downregulated in HCV infected livers and in Huh7 cells bearing the full length HCV replicon. HCV replication is associated with impaired Jak-STAT signalling by antiviral and cytoprotective cytokines. These effects may favour viral replication while facilitating the progression of liver disease.